OPTIMASI SETTING PARAMATER CLEANLINESS, KETEBALAN, DAN JENIS CAT PADA MATERIAL BAJA A572 TERHADAP DAYA REKAT CAT - Farizi Rachman; Bayu Wiro Karuniawan; Anggie Madhu Firdiandani (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2021)
The manufacturing process consists of several stages, one of them is the finishing stage. The finishing stage at PT. Supra Surya Indonesia consists of surface preparation process and painting process. The adhesion of the paint must meet the criteria to get good protective quality for the product. In the painting process, there are always defective products that must go through the repair stage before packing. Process parameters such as cleanliness level of the material surface and paint thickness need to be considered and the selection of the type of paint will affect the results of painting. Based on the problems above, it is necessary to research the analysis of process parameters that can optimize the value of paint adhesion. This study uses the Taguchi method so that the contribution of cleanliness parameters is 49.6995 %, paint thickness is 5.0014 %, and paint type is 40.4139 %. The optimum combination of parameters is cleanliness Sa 2 1/2, the thickness of 100 µm, and the type of phenolic epoxy paint.